Supervision Policy On Public Services At The Office Of Transportations Of North Sumatra Province - Saima Rambe; Nurul Dalimunte (LEGAL BRIEF, 2022)
This study raises the issue of Public Service Supervision Policy at the North Sumatra Provincial Transportation Service, the Supervision Policy is a provision made in an effort to determine whether the conditions of the activities carried out have reached the specified target. To reveal the research problem used secondary data and primary data with a sample of 30 people. The analytical method used is Product Moment Correlation Analysis. Individual Competence has a strong positive relationship to employee performance at the Department of Transportation of North Sumatra Province where the research results are based on a correlation test. Supervision Policy has a strong positive effect on Public Services where the research results are based on the correlation test of Public Service Supervision Policies of 0.97. compared to the critical table r product moment (n = 30) with df = 95% there are numbers r table = 0.349 where rxy = 0.97 > 0.349 this means that the Supervision Policy has a strong positive relationship to public services in North Sumatra Transportation Service Province. The results of this study suggest that the better supervision policies owned by the North Sumatra Provincial Transportation Service are formed in the dimensions of systems and work methods, repair of work errors, procedures or policies, compensation and use of work tools and facilities and followed by increased efficiency, effectiveness, fairness, responsibility and accountability of public services at the North Sumatra provincial transportation office. Policy factors for implementing work systems and methods, correcting work errors, procedures or policies, compensation and use of work tools and facilities will be followed by efficiency, effectiveness, fairness, responsibility and accountability of public services in North Sumatra provincial transportation offices.